Anatomy of Heinrich Layer 1 and its role in the last deglaciation. (30th March 2017) - Hodell, David A.; Nicholl, Joseph A.; Bontognali, Tomaso R. R.; Danino, Steffan; Dorador, Javier; Dowdeswell, Julian A.; Einsle, Joshua; Kuhlmann, Holger; Martrat, Belen; Mleneck‐Vautravers, Maryline J.; Rodríguez‐Tovar, Francisco Javier; Röhl, Ursula
Abstract: X‐ray fluorescence (XRF) core scanning and X‐ray computed tomography data were measured every 1 mm to study the structure of Heinrich Event 1 during the last deglaciation at International Ocean Discovery Program Site U1308. Heinrich Layer 1 comprises two distinct layers of ice‐rafted detritus (IRD), which are rich in detrital carbonate (DC) and poor in foraminifera. Each DC layer consists of poorly sorted, coarse‐grained clasts of IRD embedded in a dense, fine‐grained matrix of glacial rock flour that is partially cemented. The radiocarbon ages of foraminifera at the base of the two layers indicate a difference of 1400 14 C years, suggesting that they are two distinct events, but the calendar ages depend upon assumptions made for surface reservoir ages. The double peak indicates at least two distinct stages of discharge of the ice streams that drained the Laurentide Ice Sheet through Hudson Strait during HE1 or, alternatively, the discharge of two independent ice streams containing detrital carbonate. Heinrich Event 1.1 was the larger of the two events and began at ~16.2 ka (15.5–17.1 ka) when the polar North Atlantic was already cold and Atlantic Meridional Overturning Circulation (AMOC) weakened. The younger peak (H1.2) at ~15.1 ka (14.3 to 15.9 ka) was a weaker event than H1.1 that was accompanied by minor cooling. Our results support a complex history for Heinrich Stadial 1 (HS1) with reduction in AMOC during the early part (~20–16.2 ka) possibly driven by melting of European ice sheets, whereas the Laurentide Ice Sheet assumed a greater role during the latter half (~16.2–14.7 ka). Key Points: Heinrich Layer 1 is represented by a double peak in the central North Atlantic Best estimates for the ages of the two peaks are ~16.1 (H1.1) and ~15 ka (H1.2) Heinrich Event 1 cannot account for cooling and weakened AMOC during early Heinrich Stadial 1 (~20–16.1 ka)